Freaky [videorecording (Blu-Ray + DVD)] - Landon, Christopher, 1975-; Kennedy, Michael, 1980-; Vaughn, Vince; Newton, Kathryn, 1997-; Finneran, Katie; O'Connor, Celeste, 1998-; Osherovich, Misha; Ruck, Alan, 1956-; Shelton, Uriah, 1997-; Drori, Dana; Rose, Laurie; Adams, Whitney Anne; et al. (Universal Pictures Home Entertainment, 2021)
After swapping bodies with a deranged serial killer, a young girl in high school discovers she has less than 24 hours before the change becomes permanent.